Does Openness to International Financial Flows Raise Productivity Growth? - Prasad, Eswar; Kose, Ayhan; Terrones, Marco (Washington, D.C. : International Monetary Fund, 2008)
This paper provides a comprehensive analysis of the relationship between financial openness and total factor productivity (TFP) growth using an extensive dataset that includes various measures of productivity and financial openness for a large sample of countries. We find that de jure capital account openness has a robust positive effect on TFP growth. The effect of de facto financial integration on TFP growth is less clear, but this masks an important and novel result. We find strong evidence that FDI and portfolio equity liabilities boost TFP growth while external debt is actually negatively correlated with TFP growth. The negative relationship between external debt liabilities and TFP growth is attenuated in economies with higher levels of financial development and better institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet